(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The presented study is focused on an optimization analysis of a complex automotive component consisting of two parts with different materials. The research examines the impact of various runner configurations, cooling parameters, gate positioning, and melt temperature distribution within the mold. The paper emphasizes the advantages and applications of integrating such optimization techniques. Parametric and geometric optimization of the model is done, along with the evaluation of simulated filling processes, as clarified for the paper's objectives. Additionally, a methodical approach is outlined, clearing the process of operational rate selection, material property analysis, control parameter establishment, and preemptive simulations.